Computational analysis dynamics fluid of flow in dam using COMSOL Multiphysics. Issue 1 (1st January 2023) - Masna,; Tulus,; Sawal,
Abstract: One way to utilize river flows in Indonesia is to make a dam to get benefits in various fields. The river flow that enters the dam and which will flow again makes flow in the dam which causes a fluid dynamics. The fluid dynamics that occur in dams produce several events such as precipitation, flow turbulence, and so on. To see how the flow is, in this study a simulation was carried out by making a dam model followed by fluid dynamics analysis of the dam model. Then it will be solved by the finite element method. In its completion, a COMSOL Multiphysics program is used that applies the finite element method to get results and simulations. The results to be obtained using the mesh transfer method. Where mesh displacement applies the speed of surface displacement as the velocity of fluid flow when entering, the solution to the equation in mesh displacement uses displacement on the node, and the Navier Stokes equation is solved by substituting the displacement equation on the mesh. The results obtained at an interval of approximately 3 seconds with a speed of 0.7 m/s will produce turbulence flow at the dam where the maximum speed on the surface is 0.4 m/s. As a result, if there are other elements in the flow other than water, it will cause mixing of substances in the middle of the dam in 3 seconds and then precipitation will occur. In the next study, different dam models will be carried out and have a faster flow rate.